Particularities of the Forensic Science Investigation of Transnational Serious Crimes - Magherescu, Delia (IUS ET SCIENTIA, 2020)
The issue of serious crimes committed in a transnational or even supranational manner, as the specialists have stated before, involves more interest from the forensic science experts in their approaches in order to find a way of balance in analyzing and investigating the phenomena arose in the field of various criminality more spread currently. They have been taken into account by the forensic experts due to the fact that there are dilemmas they are confronted with. One of these leads with the idea of how serious crimes are investigated by means of forensic science's methods, technologies in the crimes trace of unauthorized technological transfer of nuclear or radioactive sources from the profile stations to the organized criminal groups' receivers. The current paper focuses on an atypical situation less discussed among the forensic experts facing serious states on achieving the forensic science examinations. It is about the technological transfer of nuclear or radioactive resources the organized criminal groups use in order to stock and sell it to the terrorist organizations, interested in manufacturing the mass destroying arms. The current paper approaches the scientific potential resources the forensic science provides on unconventional barriers of organized criminal groups in purpose to investigate from the forensic science's point of view the aspects of unauthorized technological transfer, collecting and stocking the nuclear and radioactive materials.